1961
DOI: 10.1177/00220345610400021501
|View full text |Cite
|
Sign up to set email alerts
|

The Pathways of the Early Carious Process. I. Histologic Study

Abstract: There are generally said to be three components of the structural unit of enamel: the interprismatic substance, a continuous phase which in cross-section looks like a net; a separate phase, the rods, which have rather complex cross-sections; and a third phase, the sheath, which more or less completely covers each prism and is accordingly seen in cross-sections as a more or less complete ring around each rod. The sheath, after the early stages of histogenesis, is space rather than membrane and becomes smaller a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Therefore the reduction in MP values observed in WSLs, which was also supported by BS-SEM observations (data not shown), was due to the loss of mineral rather than change of microstructure in demineralised enamel. Previous observations of WSLs using microradiography [Darling, 1958;Coolidge and Wallace, 1961] and BS-SEM [Pearce and Nelson, 1989] have clearly shown that this is not a homogeneous process of mineral dissolution within the body of the lesion. These authors have shown that typically, at the leading edge of the WSL, dissolution is greatest at the rod boundary, whereas behind this leading edge, at the body of the WSL, general dissolution is occurring and remineralisation of the rodboundary area is taking place.…”
Section: Mechanismsmentioning
confidence: 94%
“…Therefore the reduction in MP values observed in WSLs, which was also supported by BS-SEM observations (data not shown), was due to the loss of mineral rather than change of microstructure in demineralised enamel. Previous observations of WSLs using microradiography [Darling, 1958;Coolidge and Wallace, 1961] and BS-SEM [Pearce and Nelson, 1989] have clearly shown that this is not a homogeneous process of mineral dissolution within the body of the lesion. These authors have shown that typically, at the leading edge of the WSL, dissolution is greatest at the rod boundary, whereas behind this leading edge, at the body of the WSL, general dissolution is occurring and remineralisation of the rodboundary area is taking place.…”
Section: Mechanismsmentioning
confidence: 94%
“…(1) There may be separate components with different solubilities in the sense that if the components reach equilibrium with the solvent more of one component than of the other will have dissolved. (2) The distribution or state of one component may be such that it dissolves more rapidly than the other. (3) A compound may dissolve in such a way that its eomposition changes continuously.…”
mentioning
confidence: 99%